2015
DOI: 10.3109/08916934.2015.1101071
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17Ars2275913, Interleukin-17Frs763780 and rs2397084 gene polymorphisms as possible risk factors in Juvenile lupus and lupus related nephritis

Abstract: The GGAGAA combined genotype and the GGA haplotype of IL-17A rs2275913, IL-17F rs763780 and rs2397084 can be considered risk factors for the development of SLE in Egyptian children. IL-17A rs2275913, IL-17F rs763780 and rs2397084 are not related to the LN development, SLE disease activity or overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…Discrepancies in genotype frequencies between reports may be explained by the heterogeneity of the analyses diseases, distinct ethnicities as well as limited sample size. Moreover, the other two SNPs -IL-17F rs2397084 A/G and IL-23R rs10489629 G/A were not observed to be associated with SLE, whit is a concordance with others studies [14][15][16][17][18][19]. The results of this study showed also no significant differences between SLE patients and control subjects in genotypes distribution and allele frequencies for the IL-23A rs11171806 G/A polymorphism.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Discrepancies in genotype frequencies between reports may be explained by the heterogeneity of the analyses diseases, distinct ethnicities as well as limited sample size. Moreover, the other two SNPs -IL-17F rs2397084 A/G and IL-23R rs10489629 G/A were not observed to be associated with SLE, whit is a concordance with others studies [14][15][16][17][18][19]. The results of this study showed also no significant differences between SLE patients and control subjects in genotypes distribution and allele frequencies for the IL-23A rs11171806 G/A polymorphism.…”
Section: Discussionsupporting
confidence: 89%
“…Structural, quantitative, or regulatory polymorphisms at the IL-17F, IL-23A and/or IL-23R locus may lead to an incorrect of functional Th17 cells and contribute to the susceptibility to some autoimmune conditions. The IL-17F and IL-23R gene polymorphisms, including all examined here have been studied in different ethnic group [14][15][16][17][18]. The results of this study showed significant differences between SLE patients and healthy subjects in genotype distribution and allele frequencies for the IL-23R rs1884444 G/T and IL-17F rs763780 A/G polymorphisms.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The AA genotype of the rs2275913 SNP of the IL‐17A gene is reportedly associated with a higher risk of asthma, bronchiolitis, ulcerative colitis, digestive cancer, gastric cancer, and cervical cancer . Other studies reported that the rs2275913 SNP had no association with pediatric systemic lupus erythematosus disease activity or cervical cancer and had opposite effects on rheumatoid arthritis, post‐bronchiolitis asthma at 11‐13 years of age and colorectal cancer . Overall, the AA genotype of the rs2275913 SNP appears to contribute to greater inflammation, leading to autoimmune‐related inflammatory diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…IL17A is the hallmark of Th17 response and its gene is located on chromosome 6p12.1 and contains three exons and two introns (Liu et al., ). IL17A G197A (rs2275913) is the most studied IL17A SNP and had been associated with a higher susceptibility to several systemic diseases such as gastric cancer (Liu et al., ), Crohn's disease and ulcerative colitis (Zhang et al., ), juvenile systemic lupus erythematosus (Hammad et al., ), and pulmonary tuberculosis (Shi & Zhang, ), but little is known regarding its role in oral diseases.…”
Section: Introductionmentioning
confidence: 99%